2013
DOI: 10.1128/aac.00044-13
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Guides Rational Development of a Simplified Cell Culture Medium for Drug Screening against Trypanosoma brucei

Abstract: dIn vitro culture methods underpin many experimental approaches to biology and drug discovery. The modification of established cell culture methods to make them more biologically relevant or to optimize growth is traditionally a laborious task. Emerging metabolomic technology enables the rapid evaluation of intra-and extracellular metabolites and can be applied to the rational development of cell culture media. In this study, untargeted semiquantitative and targeted quantitative metabolomic analyses of fresh a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(142 citation statements)
references
References 52 publications
6
136
0
Order By: Relevance
“…The high consumption of tryptophan and phenylalanine by bloodstream form trypanosomes (19,21,22,25) suggested that the abnormal levels of aromatic ketoacids present in infected animals are transamination products generated by the parasites, but this has never been directly demonstrated. Therefore, aromatic ketoacid production by T. brucei incubated with tryptophan, tyrosine, or phenylalanine was measured directly using NAD-linked aromatic α-hydroxy acid dehydrogenase (26).…”
Section: Aromatic Ketoacids Are Produced By Transamination Catalyzed mentioning
confidence: 99%
“…The high consumption of tryptophan and phenylalanine by bloodstream form trypanosomes (19,21,22,25) suggested that the abnormal levels of aromatic ketoacids present in infected animals are transamination products generated by the parasites, but this has never been directly demonstrated. Therefore, aromatic ketoacid production by T. brucei incubated with tryptophan, tyrosine, or phenylalanine was measured directly using NAD-linked aromatic α-hydroxy acid dehydrogenase (26).…”
Section: Aromatic Ketoacids Are Produced By Transamination Catalyzed mentioning
confidence: 99%
“…The new medium, CMM, provided comparable growth rates to HMI-11 and showed that parasites were much more sensitive to several drugs in a minimal medium where nutrients are not in excess. 17 These media are also useful for flux analyses in which stable-isotope labeled metabolites are tracked in real time through metabolic pathways. 4 In the absence of a minimal medium, defined media 21,22 are used to ensure that knowledge of the source of nutrients can be traced back to the cell under study or the medium in which the cells are grown.…”
Section: Experimental Designmentioning
confidence: 99%
“…[17][18][19][20] Metabolomics has recently been used to show that bloodstream-form T. brucei used only glucose, cysteine, glutamine, and aromatic amino acids from the HMI-11 classically used to culture bloodstream-form trypanosomes. 17 A minimal medium comprising these nutrients, salts, buffer, but still requiring serum was devised. The new medium, CMM, provided comparable growth rates to HMI-11 and showed that parasites were much more sensitive to several drugs in a minimal medium where nutrients are not in excess.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations